Hydrated and dehydrated Ca-coordination polymers based on benzene-dicarboxylates: mechanochemical synthesis, structure refinement, and spectroscopic characterization. Issue 7 (25th January 2018) - Al-Terkawi, Abdal-Azim; Scholz, Gudrun; Prinz, Carsten; Zimathies, Annett; Emmerling, Franziska; Kemnitz, Erhard
Abstract : Hydrated Ca-CPs were synthesized by milling. Dehydrated phases were obtained by thermal treatments in reversible processes. Abstract : A series of Ca-based coordination polymers were prepared mechanochemically by milling Ca(OH)2 with phthalic acid (H2 o BDC), isophthalic acid (H2 m BDC), and terephthalic acid (H2 p BDC). The hydrated compounds [Ca( o BDC)(H2 O)] (1 ), [Ca( m BDC)(H2 O)3.4 ] (2 ), and [Ca( p BDC)(H2 O)3 ] (3 ) were prepared for the first time via mechanochemical routes. The refined structures were validated by extended X-ray absorption data. The new dehydrated compound [Ca( o BDC)] (1 -H 2 O ), obtained after the thermal post-treatment of1 in a reversible phase transition process, was determined ab initio based on the powder X-ray diffraction (PXRD) data. The materials were thoroughly characterized using elemental analysis, thermal analysis, and spectroscopic methods: magic-angle spinning NMR and attenuated total reflection-infrared spectroscopy. The specific surface areas and sorption properties of the hydrated and dehydrated samples were determined using the isotherms of gas sorption and dynamic vapor sorption measurements.